The impact of digital empowerment on open innovation performance of enterprises from the perspective of SOR - Lingling, Liang; Ye, Li (Frontiers in Psychology, 2023)
Introduction As China’s digital transformation index continues to climb and market openness increases, the active implementation of open innovation embedded in digital innovation eco-networks is key to implementing sustainable innovation-driven strategies. The widespread use of digital technologies has broken through the traditional closed boundaries of enterprises and enhanced technology exchange, information communication and R&D collaboration with other innovation agents.However, many enterprises’ digital empowerment efforts only stay at the level of digital technology, but do not rise to the level of corporate strategy. How to comprehensively promote the change of enterprise digital empowerment and help enterprises build a sustainable open innovation ecosystem needs further research. Methods This article uses the structure equation model and the necessary condition analysis methods to combine the stimulus-organization-reaction (SOR) theory to analyze the conduction mechanism of digital authorization to open innovation from a cognitive perspective. Results (1) In the era of digital economy, digital empowerment emphasizes the initiative and adaptability of enterprises, and explores a sustainable digital road suitable for enterprises themselves; (2) Organizational emotional ability and organizational disordered atmosphere play a mediating role between digital empowerment and open innovation, but organizational emotional ability has a positive impact on open innovation, while organizational disordered atmosphere is the opposite. (3) Organizational identity positively regulates the relationship between the disordered atmosphere and open innovation. Discussion The development of digital technology has adapted deviations with traditional management models. Organizing the investment in digital construction should also pay attention to the digital training and digital thinking of organizational members.Organizations should provide organizational support through various channels, enhance employees’ organizational commitments to create a relationship -shaped psychological contract, regularly carry out digital education and organizational culture, reduce the differential atmosphere between teams, enhance the team’s awareness of cooperation and trust in the teamAnd overall consciousness.